In situ production of visible light absorbing Ti-based nanoparticles in solution and in a photopolymerizable cationic matrix. Issue 26 (27th February 2015) - Lalevée, J.; Poupart, R.; Bourgon, J.; Fouassier, J.-P.; Versace, D.-L.
Abstract : The synthesis of visible-light absorbing Ti NPs from photoinitiating systems based on titanium(iv ) propoxide derivatives/iodonium salt under light activation. Abstract : A novel straightforward approach has been proposed to generate in situ, under light activation and in aerated media, visible-light absorbing and well-defined titanium-based nanoparticles (NPs) in solution and in an epoxide matrix using titanium derivative complexes/iodonium salt photoinitiating systems. The nature of the solvent and oxygen plays a decisive role, and two mechanisms involved in these syntheses are operative, i.e. a photofragmentation/addition process (in toluene and isopropanol) and a photoinduced sol–gel reaction (in isopropanol).